Study Atas Putusan No 254/PID.B/2017/PN LLG Kepemilikan Senjata Tajam di Pengadilan Negeri Lubuk Linggau - Apriansyah, Apriansyah; Romli, Romli; Yusuf, Hambali (Hukum dan Masyarakat Madani, 2025)
This research was conducted at the Lubuk Linggau District Court, South Sumatra. This study aims to examine and analyze the legal rules on criminal acts without the right to carry sharp weapons in the Musi Rawas Lubuk Linggau area. The method used in this study is a normative legal research method that is descriptive analysis, namely research conducted by examining library materials (secondary data) or library legal research. The types and sources of data used in this study are Types of data, Data sources and, data collection techniques used in this study using library research.  Based on the research results, in terms of ownership of sharp weapons, anyone without exception can be punished in this case, and when is a person declared as a perpetrator of the crime of ownership of sharp weapons as written in the rules as regulated and threatened with criminal penalties in Article 2 paragraph (1) of Law/drt/No.12 of 1951. Like the case study discussed in this case, the case of "Without the Right to Carry Sharp Weapons" is proven written in article two, it is explained that anyone who without the right brings into Indonesia, makes, receives, tries to obtain it, hands over or tries to hand over, controls, carries, has a stock of it or has in his possession, stores, transports, hides, uses or removes from Indonesia a weapon for striking, stabbing, or stabbing weapon (slag, steek of stoot wapen), is punished with a maximum prison sentence of ten years. The conclusion in this case is that anyone who does not have a permit to own sharp weapons and has no relationship with his work is declared to have committed the crime of possessing sharp weapons without a permit.  .That in the case of possession of sharp weapons without a permit, it basically must be further investigated in order to fulfill the elements of justice from various parties, namely the judge's consideration must look at two sides, which in this case the consideration should no longer look at what kind of unrest is a threat to residents so that the defendant is reported, and see what caused the defendant to carry a sharp weapon on the grounds of being on guard. Because if we look at it now, the increasing number of crimes that occur makes self-protection necessary. Keywords: Sharp Weapons, Lubuk Linggau District Court